1988
DOI: 10.1128/mcb.8.6.2472
|View full text |Cite
|
Sign up to set email alerts
|

Relationship among guanine nucleotide exchange, GTP hydrolysis, and transforming potential of mutated ras proteins.

Abstract: The effect of a series of mutations on the transforming potential of normal human rasH has been compared with their effects on GTPase and guanine nucleotide exchange rates of p21. The mutation Val-146 resulted in partial activation of transforming potential which could be attributed to a >1,000-fold-increased rate of nucleotide exchange in the absence of an effect on GTPase. In contrast, the more modest enhancement of exchange rate (-100-fold) which resulted from the mutation Met-14 did not affect biological a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
140
1

Year Published

1991
1991
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(152 citation statements)
references
References 21 publications
(59 reference statements)
11
140
1
Order By: Relevance
“…This difference was statistically significant. In agreement with our findings, a recent report showed that an in vitro mutagenized H-ras gene with a mutation in codon 146 had less transforming activity than did a ras gene with a codon 12 mutation (27).…”
Section: Biological Activity Of Ras Mutated At Codon 146supporting
confidence: 82%
“…This difference was statistically significant. In agreement with our findings, a recent report showed that an in vitro mutagenized H-ras gene with a mutation in codon 146 had less transforming activity than did a ras gene with a codon 12 mutation (27).…”
Section: Biological Activity Of Ras Mutated At Codon 146supporting
confidence: 82%
“…All the cells were then exposed to P. aeruginosa for 6 hr. Forty hours after being transfected, HM3 cells were either exposed or not exposed to PAO1 culture supernatant (CS)with a dominant-negative mutant form of Ras (RasN17) (25) reduced the response by 80% (Fig. 2C), and cotransfection with a dominant-negative mutant form of c-Src (SrcRF) inhibited the response by 45% (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the nucleotide exchange rate of both p.K117R and p.A146V HRAS is increased, relative to wild type. 13,27,28 However, the transformational potential of p.A146V HRAS is partially activated, 27 whereas that of p.K117R-HRAS is not; its transformational activity is instead similar to that of GTPase impaired mutants. 28 Our results and those of other reports suggest that p.K117R and p.A146T have milder effects on downstream effectors than do mutations in codon 12/13.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with p.K117R or p.A146V had a milder and more unusual CS phenotype, compared with patients with mutations in codon 12 or 13. Though detailed analyses of some mutants have been performed, 13,[25][26][27][28] a comprehensive comparison of the substitutions identified in patients with CS has not been conducted.…”
Section: Introductionmentioning
confidence: 99%